Medkulturni položaj mladih, ki se šolajo v slovenskem jeziku v Italiji - Vidau, Zaira (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2015)
The article presents the opinions of youth studying in Slovene language in Italy about intercultural relations with the majority population in the last decade. The latter comes to light from the analysis of statements which were part of empirical studies in 2011 and 2003 among students attending Slovene high schools in Trieste (Trst) and Gorizia (Gorica) and a group of pupils that attended the bilingual school in San Pietro al Natisone (Špeter). The author starts with a literature analysis on their identity and sociological features. The paper shows that the effects of the cultural and linguistic exclusion between the two communities are still perceived. The investigated "skeptics" think that the majority population still discriminates the Slovene minority and that the communities live mostly separated. The number of investigated "optimists" is slightly higher. On the contrary, they consider that the majority population does not discriminate the Slovene culture and language. They maintain that the majority population is respectful of the Slovene presence and that the two communities are less divided than in the past.
Keywords: Italija; Italy; slovenska manjšina; zamejski Slovenci; mladi; medkulturni odnosi